2011
DOI: 10.1088/0957-4484/22/36/365201
|View full text |Cite
|
Sign up to set email alerts
|

Toward graphene-based quantum interference devices

Abstract: Abstract.A new type of quantum interference device based on a graphene nanoring in which all edges are of the same type is studied theoretically. The superposition of the electron wavefunction propagating from the source to the drain along the two arms of the nanoring gives rise to interesting interference effects. We show that a side-gate voltage applied across the ring allows for control of the interference pattern at the drain. The electron current between the two leads can therefore be modulated by the sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 36 publications
0
54
0
Order By: Relevance
“…In this case the band structure has a width-dependent gap and the corresponding dispersion relation in the vicinity of the gap is parabolic. This energy spectrum is typical for conventional semiconductors and we showed that it presents more robust and promising transmission patterns for transport control and applications [27].…”
Section: Model and Formalismmentioning
confidence: 72%
See 1 more Smart Citation
“…In this case the band structure has a width-dependent gap and the corresponding dispersion relation in the vicinity of the gap is parabolic. This energy spectrum is typical for conventional semiconductors and we showed that it presents more robust and promising transmission patterns for transport control and applications [27].…”
Section: Model and Formalismmentioning
confidence: 72%
“…This voltage allows us to control the current in the device, as thoroughly discussed in Refs. [27,28]. Assuming that electron-phonon scattering in our samples is reduced, we consider electrons in the fully coherent regime transferring ballistically through the system.…”
Section: Model and Formalismmentioning
confidence: 99%
“…Air molecules, substrate impurities, and random boundaries affect the transport properties of monolayer graphene, preventing the realization of nanoelectronic applications (quantum interface device). 16,17 Additionally, it is more difficult to prepare large-scale monolayer graphene than multilayer graphene. As such, we have studied the effects of Ga ion irradiation on multilayer graphene.…”
Section: Introductionmentioning
confidence: 99%
“…17 as well as in in Ref. 33, where it was proposed to utilize the electrostatic Aharonov-Bohm effect via side gates-such as already realized experimentally in Ref. 18-for application in a quantum interference transistor with high on/off ratio made of a hexagonal graphene ring structure with perfect edges, where armchair edges were found to be preferable.…”
mentioning
confidence: 97%